(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. The article examines the main problems and risks of decentralization in Ukraine. The process of decentralization of public administration and redistribution of powers is analyzed. The importance of decentralization reform in the process of forming local self - government is proved. The essence, content and purpose of decentralization reform are analyzed, as well as the two stages into which the reform is divided. The main tasks of the reform and its advantages are determined. The purpose of the article is to analyze the process of decentralization of power, disclosure of the content and purpose of the reform. Identify the main issues and problems that arise in the process of decentralization reform. Results. Decentralization reform in Ukraine helps to build effective relations between the central government and local governments. Decentralization enables local and regional self-government bodies to expand and strengthen their rights. The main advantages of decentralization reform are certainly the protection of human rights. The efficiency of local self-government bodies has increased, as they have been given local powers. Socio-economic development has also been improved and democratic procedures strengthened. However, in the process of implementing the reform there were certain problems, namely: perception of the reform by the people; inconsistency of powers between executive bodies, governing bodies in united territorial communities, local self-government bodies, district councils and district state administrations; lack of quality staff, low qualification of local governments and employees in the united territorial communities; state control over the activities of local self-government. The results of the decentralization reform have strengthened the interest of local governments in increasing revenues to local budgets, finding reserves to fill them, and improving the efficiency of tax and fee administration. Conclusions. As a result, we can say that decentralization makes it possible to form independent and capable communities. Local governments, thanks to their powers, can independently address issues of local life, the role of citizens, their influence on the processes of decision-making and implementation to ensure the conditions of social and economic development of society have increased. The decentralization reform contributes to the improvement of the lives of Ukrainian citizens, the building of a legal, modern, efficient, competitive state.